2020
DOI: 10.1111/head.13902
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Headaches Associated With SARS‐CoV‐2 Infection: Study of Healthcare Professionals

Abstract: Background Series of patients with SARS‐CoV‐2 infection report headache in 6%‐15% of cases, although some data suggest that the actual frequency is higher, and that headache is not associated with fever. No study published to date has analyzed the characteristics of headache in these patients. Objective To analyze the characteristics of COVID‐19 related headaches. Methods We conducted a survey of Spaniard healthcare professionals who have been infected by SARS‐CoV‐2 and presented headache during the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 41 publications
10
83
1
7
Order By: Relevance
“…We propose that the impact of headache in COVID-19 prognosis should be studied in deeper detail. Compared with other symptoms, headache might have different phenotypes and each presentation might have a different meaning [39,40]. We hypothesize that the impact of headache on prognosis might be linked to the causes of headache [41].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the impact of headache in COVID-19 prognosis should be studied in deeper detail. Compared with other symptoms, headache might have different phenotypes and each presentation might have a different meaning [39,40]. We hypothesize that the impact of headache on prognosis might be linked to the causes of headache [41].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews and meta-analyses showed that headache and dizziness are among the most frequent neurological symptoms affecting COVID-19 patients (71,72). Interestingly, headache can occur even in the absence of fever and can be manifested as a migraine, tension-type, or cluster headache (73).…”
Section: Non-specific Neurological Symptomsmentioning
confidence: 99%
“…In general, three main primary headaches are observed in COVID-19 patients i.e. migraine, cluster headache and tension-type headache [137][138][139][140] . No fixed mechanisms have been reported on how these headaches emerge in COVID-19 patients.…”
Section: Headache Pathogenesis In Covid-19mentioning
confidence: 99%
“…In regards to the headache characteristics presented by COVID-19 patients compared to the headache induced by other viral infections, no apparent differences could be observed. Headache in COVID-19 could be worsened by physical or head movement, felt in either the entire head (holocranial) or unilaterally (hemicranial) and and the pain is typically pressing or tightening 139 . It is hypothesized that headaches occurring in COVID-19 patients might be the result of the same mechanisms as observed in influenza A and influenza B infections, which could be related to the activity of cytokines 173,[185][186][187] .…”
Section: Headache Pathogenesis In Covid-19mentioning
confidence: 99%